Filler Wetting in Miscible ESBR/SSBR Blends and Its Effect on Mechanical Properties. Issue 4 (29th January 2016) - Le, Hai Hong; Reincke, Katrin; Das, Amit; Stöckelhuber, Klaus‐Werner; Wiessner, Swen; Pham, Tung; Do, Quang Khang; Tung Hoang, Xuan; Grellmann, Wolfgang; Heinrich, Gert; Radusch, Hans‐Joachim
Abstract : The silica surface fraction S B(ESBR) and S B(SSBR), which is wetted by ESSBR and SSBR, respectively, varies with ESBR fraction in ESBR/SSBR blends. It is obvious that in all blends the silica surface is dominantly wetted by the SSBR component. The illustrated structure of the blends investigated shows a morphology with an SSBR‐rich interphase and ESBR‐rich matrix. Abstract : The selective wetting behavior of silica in emulsion styrene butadiene rubber (ESBR)/solution styrene butadiene rubber (SSBR) blends is characterized by the wetting concept, which is further developed for filled blends based on miscible rubbers. It is found that not only the chemical rubber – filler affinity but also the topology of the filler surface significantly influences the selective filler wetting in rubber blends. The nanopore structure of the silica surface has been recognized as the main reason for the difference in the wetting behavior of the branched ESBR molecules and linear SSBR molecules. However, the effect of nanopore structure becomes more significant in the presence of silane. It is discussed that the adsorption of silane on silica surface constricts the nanopore to some extent that hinders effectively the space filling of the nanopores by the branched ESBR molecules but not by the linear SSBR molecules. As a result, in silanized ESBR/SSBR blends the dominant wetting of silica surface by the tightly bonded layer of SSBR molecules causes a low‐energy dissipation in the rubber–filler interphase. That imparts the low rolling resistance to the blends similar to that of a silica‐filled SSBR compound, while the ESBR ‐ rich matrix warrants the good tensile behavior, i.e., good abrasion and wear resistance of the blends.